Intestinal microbiota dysbiosis contributes to the liver damage in subchronic arsenic-exposed mice - Dong Ling; Luo Peng; Zhang Aihua (Acta Biochimica et Biophysica Sinica)
There is an extensive amount of evidence that links changes in the intestinal microbiota structure to the progression and pathophysiology of many liver diseases. However, comprehensive analysis of gut flora dysbiosis in arsenic-induced hepatotoxicity is lacking. Herein, C57BL/6 mice are exposed to arsenic (1, 2, or 4 mg/kg) for 12 weeks, after which fecal microbiota transplantation (FMT) study is conducted to confirm the roles of the intestinal microbiome in pathology. Treatment with arsenic results in pathological and histological changes in the liver, such as inflammatory cell infiltration and decreased levels of TP and CHE but increased levels of ALP, GGT, TBA, AST, and ALT. Arsenic causes an increase in the relative abundance of Escherichia-Shigella, Klebsiella and Blautia, but a decrease in the relative abundance of Muribaculum and Lactobacillus. In arsenic-exposed mice, protein expressions of Occludin, ZO-1, and MUC2 are significantly decreased, but the level of FITC in serum is increased, and FITC fluorescence is extensively dispersed in the intestinal tract. Importantly, FMT experiments show that mice gavaged with stool from arsenic-treated mice exhibit severe inflammatory cell infiltration in liver tissues. Arsenic-manipulated gut microbiota transplantation markedly facilitates gut flora dysbiosis in the recipient mice, including an up-regulation in Escherichia-Shigella and Bacteroides, and a down-regulation in Lactobacillus and Desulfovibrio. In parallel with the intestinal microbiota wreck, protein expressions of Occludin, ZO-1, and MUC2 are decreased. Our findings suggest that subchronic exposure to arsenic can affect the homeostasis of the intestinal microbiota, induce intestinal barrier dysfunction, increase intestinal permeability, and cause damage to liver tissues in mice.